Molecular genetics of human chromosome 16. Issue 8 (August 1987) - Sutherland, G R; Reeders, S; Hyland, V J; Callen, D F; Fratini, A; Mulley, J C
Abstract : The major diseases mapped to chromosome 16 are adult polycystic kidney disease and those resulting from mutations in the alpha globin complex. There are at least six other less important genetic diseases which map to this chromosome. The adenine phosphoribosyltransferase gene allows for selection of chromosome 16 in somatic cell hybrids and a hybrid panel is available which segments the chromosome into six regions to facilitate gene mapping. Genes which have been mapped to this chromosome or which have had their location redefined since HGM8 include APRT, TAT, MT, HBA, PKD1, CTRB, PGP, HAGH, HP, PKCB, and at least 19 cloned DNA sequences. There are RFLPs at 13 loci which have been regionally mapped and can be used for linkage studies.